Tryptophan Kynurenine Pathway-Based Imaging Agents for Brain Disorders and Oncology—From Bench to Bedside - Erik Stauff; Wenqi Xu; Heidi H. Kecskemethy; Sigrid A. Langhans; Vinay V. R. Kandula; Lauren W. Averill; Xuyi Yue (Biomolecules)
Tryptophan (Trp)-based radiotracers have excellent potential for imaging many different types of brain pathology because of their involvement with both the serotonergic and kynurenine (KYN) pathways. However, radiotracers specific to the kynurenine metabolism pathway are limited. In addition, historically Trp-based radiopharmaceuticals were synthesized with the short-lived isotope carbon-11. A newer generation of Trp-based imaging agents using the longer half-lived and commercially available isotopes, such as fluorine-18 and iodine-124, are being developed. The newly developed amino acid-based tracers have been demonstrated to have favorable radiochemical and imaging characteristics in pre-clinical studies. However, many barriers still exist in the clinical translation of KYN pathway-specific radiotracers.